Retention and Recall of Lexicon Using Semantic Maps - Udaya, Muthyala (Education and Development, 2022)
Semantic maps ensure a high potential to facilitate enhanced quality of understanding words. ESL students are often presented with new English vocabulary items that are many times pre-organized in sets of semantically related words. Although there is an assumption that word grouping facilitates the activities for vocabulary learning, little or no empirical justification is offered by researchers in support of employing this teaching technique. This study aims to examine to what extent semantic relatedness influences ESL vocabulary recall and retention for middle school students of Telangana. The current study was conducted with 30 seventh grade students who were divided into two groups to compare the effects of presenting semantic maps and wordlists for reading comprehension activities. The results reveal that both teaching strategies have positive effects on vocabulary recall and retention. Between these two strategies semantic mapping was found to yield better results on recall. The difference between the groups can be explained from the perspective of information process theory and memory model. Significant learning and effectiveness of semantic maps was found in the experiment group.